10 Answers

(4x − 6) − (5x + 1)
4x − 6 + 5x – 1
(4x – 5x) + (6 – 1)
1x – 7
x – 7

Simplify? Lol. What do you propose simplify? Do they provide a # to place into x? or you will possibly desire to easily combine like words. (4x – 6) + (5x+a million) = 4x – 6 + 5x + a million = 4x + 5x 6 + a million = 9x – 5 9x – 5 might desire to be the simplifed answer if there is no # to place into x. yet while they do provide you an x only plug it in and you will possibly desire to be sturdy. ;]

(4x6)(5x+1)=0
4x65x1=0
4x5x61=0
x7=0
7=x
Answer: x=7

= (4x – 6) – (5x + 1)
= 4x – 6 – 5x – 1
= 4x – 5x – 6 – 1
= x – 7
= (x + 7)

(4x − 6) − (5x + 1)
(4x − 6) − 5x – 1
4x − 6 − 5x – 1
– x – 7

2x – 6x
Source(s): I think…